2004
DOI: 10.1093/jnci/djh334
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking, Alcohol Drinking, Hepatitis B, and Risk for Hepatocellular Carcinoma in Korea

Abstract: Cigarette smoking, heavy alcohol consumption, and HBsAg were independently associated with increased risk of mortality from hepatocellular carcinoma but did not interact synergistically. The relatively higher increase in mortality from hepatocellular carcinoma in HBsAg-seropositive women compared with men merits further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
141
2
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(152 citation statements)
references
References 12 publications
6
141
2
3
Order By: Relevance
“…[7][8][9][11][12][13] In our study, at ethanol intakes of 46 g/day or more, the data are strongly supportive of an association between alcohol consumption and poor survival in HCC patients. The relationship between cigarette smoking and the development of HCC has been examined in many studies in both low-and high-incidence HCC areas and the results have been mixed, [6][7][8][9][10][11] but evidence for a role of smoking in the etiology of HCC has been noted in two large prospective cohort studies conducted in areas where HBV infection is common. 6,7 Consistent with our study, a previous cohort study based on data collected as part of an insurance plan with a mean follow-up of 3 years has also indicated a deleterious effect of both smoking and alcohol consumption on survival in HCC.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…[7][8][9][11][12][13] In our study, at ethanol intakes of 46 g/day or more, the data are strongly supportive of an association between alcohol consumption and poor survival in HCC patients. The relationship between cigarette smoking and the development of HCC has been examined in many studies in both low-and high-incidence HCC areas and the results have been mixed, [6][7][8][9][10][11] but evidence for a role of smoking in the etiology of HCC has been noted in two large prospective cohort studies conducted in areas where HBV infection is common. 6,7 Consistent with our study, a previous cohort study based on data collected as part of an insurance plan with a mean follow-up of 3 years has also indicated a deleterious effect of both smoking and alcohol consumption on survival in HCC.…”
Section: Discussionsupporting
confidence: 81%
“…24 Chronic heavy alcohol drinking, defined as 60-80 g/day for prolonged period, is a cause of liver cirrhosis and an important risk factor for progression through cirrhosis to HCC. 7,9,[11][12][13][14] However, there is controversy about the magnitude of HCC risk associated with low to moderate alcohol intake. [7][8][9][11][12][13] In our study, at ethanol intakes of 46 g/day or more, the data are strongly supportive of an association between alcohol consumption and poor survival in HCC patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Large population-based cohort studies performed in East Asia showed no interaction between alcohol consumption and HBV infection on HCC risk (Yu et al, 1997;Sun et al, 1999;Evans et al, 2002;Wang et al, 2003;Jee et al, 2004). Low levels of alcohol consumption were, however, defined in these studies for 'exposed' subjects: 25 g/day (Jee et al, 2004), 'habitual' or 'weekly' consumption (Yu et al, 1997;Sun et al, 1999;Evans et al, 2002;Wang et al, 2003). Therefore, no conclusion can be drawn from these studies on the interaction between medium-high alcohol intake and HBV infection.…”
Section: Interaction With Hepatitis B Virusmentioning
confidence: 99%